Guide to Accreditation by the National Association for the Education of Young Children Self-Study, Validation, Accreditation. - National Association for the Education of Young Children, Washington, DC.; National Association for the Education of Young Children, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1998)
The National Academy of Early Childhood Programs, a division of the National Association for the Education of Young Children, partly achieves its goal of improving the quality of care and education of young children in group programs through its administration of a national, voluntary accreditation system for early childhood programs. This guide provides step-by-step instructions for each phase of the accreditation process: self-study, validation, and accreditation. The sections of the guide are as follows: (1) "Introduction to 'Guide to Accreditation'"; (2) "How To Do the Self-Study"; (3) "Early Childhood Classroom Observation"; (4) "Administrator Report and Center Profile"; (5) "Teaching-Staff Questionnaire"; (6) "Family Questionnaire"; (7) "How To Prepare Your Program Description"; (8) "How To Prepare for the Validation Visit"; (9) "The Accreditation Decision"; and (10) "Maintaining Accreditation and Reaccreditation." (Contains 144 references.) (KB)
Availability: NAEYC, 1509 16th Street, NW, Washington, DC 20036-1426 ($39). Tel: 800-424-2460 (Toll Free); Tel: 202-232-8777; Fax: 202-328-1846; e-mail: academy@naeyc.org; Web site: http://www.nacyc.org.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accreditation (Institutions); Accrediting Agencies; Early Childhood Education; Educational Quality; Guides; Quality Control; Self Evaluation (Groups); Standards; National Association Educ of Young Children; Day Care Quality -- National Academy of Early Childhood Programs; Guides, Non-Classroom.; Tests/Questionnaires.